2016
DOI: 10.1002/aic.15572
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent mixing in the confined swirling flow of a multi‐inlet vortex reactor

Abstract: Turbulent mixing in the confined swirling flow of a multi‐inlet vortex reactor (MIVR) was investigated using planar laser induced fluorescence (PLIF). The investigated Reynolds numbers based on the bulk inlet velocity ranged from 3290 to 8225, and the Schmidt number of the passive scalar was 1250. Measurements were taken in the MIVR at three different heights (¼, ½, and ¾ planes). The mixing characteristics and performance of the MIVR were investigated using instantaneous PLIF fields and pointwise statistics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The values are obtained at 10 mm axial plane from the bottom plate of the unit. For low solid loadings (up to 1.5 g), the gas velocity behavior is corresponding to free‐swirl motion and increases toward the central exhaust ( r = 10 mm). The flow is as such where the gas flow affects the solids flow but not vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…The values are obtained at 10 mm axial plane from the bottom plate of the unit. For low solid loadings (up to 1.5 g), the gas velocity behavior is corresponding to free‐swirl motion and increases toward the central exhaust ( r = 10 mm). The flow is as such where the gas flow affects the solids flow but not vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…Confined vortex flow finds significance in numerous industrial processes. Such flows are used for mixing (Levy and Albagli, 1991;Liu et al, 2017) as well as for the separation of two or more phases with different densities (Sommerfeld and Qiu, 1993), and also for flow stabilisation (as in swirl burners (Froud et al, 1995)). One popular application of swirldominated flow and the subject of this study is the cyclone separator.…”
Section: Introductionmentioning
confidence: 99%
“…Musa et al 17 studied the ignition and flame stability of high‐density polyethylene solid fuel with incoming swirling air through a solid fuel ramjet and found that inducing swirling flow could improve the combustion efficiency and stability. Liu et al 18 studied the mixing performance in the turbulent swirling flow of a multiinlet vortex reactor by using planar laser‐induced fluorescence (PLIF) and the mixing mechanisms in the reactor were discussed. It is noted that reports on the swirling flow in the literature mainly focus on gas mixing and few works can be found for the liquid mixing, which is more widely used in chemical production.…”
Section: Introductionmentioning
confidence: 99%